PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN DI PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI PADA TAHUN 2014-2016 - Rahmanto, Wahyu (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan, 2018)
This research aims to test the influence of Good Corporate Governance financial performance against banking company listed on the Indonesia stock exchange (BEI) in 2014 up to 2016. Independent variables from this research are the number of the Board of Commissioners, Board of Directors, the size of the company and the independent Commissioner, while the variable dependency is the financial performance. The population in this research is the entire banking company registered in BEI years 2014 to 2016. While the study sample is determined by the method of purposive sampling so that the retrieved sample company with 35 105 observations. Types of data used are secondary data obtained from www.idx.co.id. Methods of analysis used are multiple regression analysis. Based on the results of the study showed that the number of Commissioners do not affect the company's financial performance, the Board of Directors does not have an effect on the financial performance of the company, the independent Commissioner has no effect to performance corporate finance and the size effect on the financial performance of the company .